Expression of Tumour-Associated Antigens and Characteristics of T Cell Responses in Breast Carcinoma - Leong, Pooi Pooi (2005)
Breast cancer is the most common cancer among women in Malaysia. The standard conventional clinical management procedures use chemotherapy, radiotherapy and mastectomy. In the past decade, intense research towards the use of T-cell based immunotherapy as a treatment alternative has been made. The goals of our study are first to identify some of the tumour-associated antigens present in our tumour specimens from patients with infiltrating ductal carcinoma (IDC) of the breast, followed by antigenic peptide selection in order to develop an in vitro T-cell based cytotoxicity assay. At the same time, we also identified immunophenotypes of the tumour infiltrating lymphocytes (TILs) in the breast tumours. Isolated peripheral blood mononuclear cells (PBMCs) from patients with IDC were specifically stimulated with three combinations of cytokines and antibodies that were specific to the co-stimulatory molecule and HLA-A02 restricted antigen-specific peptides. Stimulated PBMCs were then used as effector cells in cytotoxicity assay using calcein-AM in which the MCF-7 breast adenocarcinoma cell line served as the target cells. Phenotypic investigation of tumour cell suspension was carried out by using specific lymphocyte cell differentiation markers. By using paraffin-embedded breast tissues (n=49), immunohistochemistry studies showed significant expression of survivin (8O.l%, p<0.00 I), cytoplasmic MUC- 1 (38.3%, p<0.05) and membranous MUC-1 (63.8%, p<0.001) in the tumour area as compared to the apparently normal adjacent tissues. These results provided a guide for antigenic peptide selection for stimulating the T cells from the blood of the patients. Together in the presence of rIL-2 and rIL-7, 4 out of 9 peripheral blood mononuclear cells (PBMCs) from the patients responded to either survivin-derived peptide (S2) or Her21neu specific peptide (H2) in a HLA-A02 restricted manner in order to produce sufficient amounts of effector cells for the subsequent cytotoxic assay. As effectorltarget (EIT) ratio increased, cytolytic activity of the effector cells became more efficient. For immunophenotypic analysis, CD8+ TILs at 23.4 -t- 2.1% was found to be the major population in TILs and the presence of its effector counterpart, CD8+CD28+ TILs significantly correlated with low incidence of metastasis (p<0.05). At the same time, we noticed the predominance of CD4+CD25+ regulatory T cells (Treg) at 55.9 + 3.9% in the Treg pool and its presence was significantly found in post-menopausal patients @<0.05). In conclusion, survivin and MUC-1 (cytoplasmic and membranous) were over-expressed in breast cancer tissues. Further investigations are needed to determine the reasons as to why only a portion of PBMCs from the patients (419) responded to the specific peptide-based stimulation and showed effective cytolytic activity towards the target breast adenocarcinoma MCF-7 cell line. It is possible that other cytokine cocktails are needed to enhance the cytolytic property of the PBMCs. We also found that infiltration of effector TILs, CD8+CD28+, significantly reduced the metastatic event. Lastly, we noted that older women (2 50 years old) tend to possess higher amount of CD4+CD25+ Treg in TILs as compared to the younger patients (< 50 years old). The higher CD4+CD5+ Treg in Til may implicate poor disease outcome in older patients. We proposed that these Treg cells contribute to tumour escape mechanism.